Relation between trihalomethane compounds and birth defects. Issue 7 (1st July 2001) - Dodds, L; King, W D
Abstract : OBJECTIVES: To evaluate the risk of birth defects relative to exposure to specific trihalomethanes in public water supplies. METHODS: A retrospective cohort study was conducted based on data from a population based perinatal database in Nova Scotia, Canada and from the results of routine water monitoring tests. The cohort consisted of women who had a singleton birth in Nova Scotia between 1988 and 1995 and who lived in an area with a municipal water supply. The birth defects analyzed included neural tube defects, cardiovascular defects, cleft defects, and chromosomal abnormalities. Two of the four trihalomethane compounds occur in large enough concentrations to be analyzed (chloroform and bromodichloromethane (BDCM)). RESULTS: Exposure to BDCM at concentrations of 20 μg/l or over was associated with an increased risk of neural tube defects (adjusted relative risk (RR) 2.5, 95% confidence interval (95% CI) 1.2 to 5.1) whereas exposure to chloroform was not. Exposure to BDCM of 20 μg/l and over was associated with decreased risks of cardiovascular anomalies (RR 0.3, 95% CI 0.2 to 0.7). There was a suggestion of an increased risk of chromosomal abnormalities associated with exposure to chloroform, and no evidence of any association between either trihalomethane compound and cleft defects. CONCLUSIONS: In this cohort, differences were found in the RR associated with exposure to chloroform and BDCM for each of the congenital anomalies under study. These findings point to the importance of examining specific byproduct compounds relative to risk for these birth outcomes and in particular implicate BDCM and other correlated disinfection byproducts in the aetiology of neural tube defects.